On the east-west slope : globalization, nationalism, racism and discourses on Eastern Europe - Melegh, Attila (Central European University Press, 2006)
Melegh's work offers a powerful analysis of the sociological and symbolic meanings of East/West in Europe after the end of the Cold War. While the fundamental poles of East and West remain, both their meaning and their relationship to one another have shifted profoundly since the late 1970s. Melegh exposes the underbelly of liberal characterizations of East/West, highlighting the polarizing effect of extreme nationalism and ethnic racism. The theoretical underpinnings of this work involve the ideas of preeminent theorists such as Karl Mannheim, Michel Foucault and more recently Maria Todorova and Iver Neumann.